2020
DOI: 10.1021/acs.organomet.0c00250
|View full text |Cite
|
Sign up to set email alerts
|

Air- and Water-Tolerant (PNP)Ir Precatalyst for the Dehydrogenative Borylation of Terminal Alkynes

Abstract: This work discloses the facile synthesis and efficacy of (PNP)IrH(OAc), a precatalyst for the dehydrogenative borylation of terminal alkynes (DHBTA). Unlike the previously reported precatalysts in the (PNP)Ir system (PNP = diarylamido/ bis(phosphine) pincer), it is air-stable in the solid state. Upon exposure to air in solution, it possesses a useful half-life on the order of 1−100 h, depending on the intensity of mixing. Airdegraded solutions of (PNP)IrH(OAc) retain DHBTA catalytic activity and selectivity up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…42,48,56 Alternatively, [(COD)M(OAc)] 2 (M = Ir, Rh) was also used in the metalation of the pincer ligands to yield the products (L)Ir(H)(OAc). 30,48 The κ 2 -acetate ligand provides protection to the sixth coordination site of the Ir center (Scheme 3, method C). Another approach (Scheme 3, method D) was described by Waterman and co-workers, who reported that the reaction of the ligand precursor L1-H with [(COE) 2 IrCl] 2 under an atmosphere of H 2 gave a high yield of (L1)Ir(H)(Cl).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…42,48,56 Alternatively, [(COD)M(OAc)] 2 (M = Ir, Rh) was also used in the metalation of the pincer ligands to yield the products (L)Ir(H)(OAc). 30,48 The κ 2 -acetate ligand provides protection to the sixth coordination site of the Ir center (Scheme 3, method C). Another approach (Scheme 3, method D) was described by Waterman and co-workers, who reported that the reaction of the ligand precursor L1-H with [(COE) 2 IrCl] 2 under an atmosphere of H 2 gave a high yield of (L1)Ir(H)(Cl).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The pyridine ligand can then be abstracted with boron trifluoride diethyl etherate (BF 3 ·OEt 2 ) to give the desired five-coordinate complex ( L )­Ir­(H)­(Cl). This approach has been reported to access clean (POCOP)Ir and (POCOP)Rh complexes. ,, Alternatively, [(COD)­M­(OAc)] 2 (M = Ir, Rh) was also used in the metalation of the pincer ligands to yield the products ( L )­Ir­(H)­(OAc). , The κ 2 -acetate ligand provides protection to the sixth coordination site of the Ir center (Scheme , method C). Another approach (Scheme , method D) was described by Waterman and co-workers, who reported that the reaction of the ligand precursor L1-H with [(COE) 2 IrCl] 2 under an atmosphere of H 2 gave a high yield of ( L1 )­Ir­(H)­(Cl) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to the common intermediates and the small differences of the barriers, the system could jump among the three cycles, making the mechanism very complicated (Scheme ). Very recently, Ozerov developed an air‐ and water‐stable (PNP)Ir precatalyst, allowing the reaction to take place under an air atmosphere, simplifying the manipulation …”
Section: Formation Of Spc−heteroatom Bondsmentioning
confidence: 99%
“…Although the catalysts from other literature reports mentioned above are based on cheaper metals (Fe, Cu, Zn), the (PNP)Ir catalysts are much more active and can be used at much lower catalyst loading while displaying equal or superior scope and chemoselectivity. We have also been able to demonstrate that (PNP)­Ir-catalyzed DHBTA exhibits reasonable tolerance of the presence of air and water and that >10 5 turnovers were possible …”
Section: Introductionmentioning
confidence: 76%